60 minutes interviews with people who inspire - Mendoza, Ivy Lisa F.; Barawid, Rachel Castro; Garcia, Angelo G.; Lim, Ronald S.; Malipot, Ina H.; Marasigan, Jaser A.; Mendoza, Ivy Lisa F. (Mandaluyong City Anvil Publishing Inc., 2013)
Interviews of influential people in the Philippines.
John L. Gokongwei -- Dr. Josette Biyo -- National Artists for Literature Virgilio S. Almario and Bienvenido L. Lumbera -- Boy Abunda -- Fr. James Bertram Reuter, Jr., SJ -- Cecilio K. Pedro -- Rico Hizon -- Judy Ann Santos -- Comedy King Dolphy -- President Benigno S. Aquino III -- Mayor Alfredo S. Lim -- Rosa Rosal -- CNN hero Efren Peñaflorida -- De La Salle's Br. Armin Luistro and Ateneo's Fr. Bienvenido Nebres -- Senator Miriam Defensor-Santiago.
Keywords: Celebrities -- Philippines -- Interviews; Interviews -- Philippines; Successful people -- Philippines -- Interviews